Variações temporais de curta escala da estrutura e dieta da ictiofauna em uma planície de maré em um estuário tropical - Silva, Adna Ferreira da (2014)
Medium scale variations in estuarine fish assemblages can be modulated by seasonal fluctuations in environmental conditions and biotic factors, but short scale variations in photoperiod and tidal cycles are also important. They can change the availability of food resources and shelter against predators and, consequently, lead to changes in fish assemblage attributes and fish diets. The effect of these short scale variations in the ichthyofauna have been investigated in several ecosystems, but their influence on fishes occurring in mudflats is poorly known. The main goal of this work is to assess the effects of temporal variation of short (diurnal and tidal) and medium (wet and dry seasons) scales in the species composition, abundance, diversity and trophic ecology of the ichthyofauna in a mudflat of the Mamanguape River estuary (Paraiba state, Northeast Brazil). Fishes were caught using beach seine hauls and the sampling design took into account the photoperiod, tidal and hydrological cycles. A total of six field sampling surveys were conducted in 2012 along the wet (May, June and July) and dry (October, November and December) seasons. In each field survey three beach seine hauls were employed in each of eight different time periods distributed along the 24h cycle. A total of 6,222 and 66 fish species were captured, being Rhinosardinia bahiensis, Lycengraulis grossidens and Eucinostomus melanopterus the most abundant ones. The analysis along the photoperiod revealed higher numerical abundance in the diurnal period, especially at midday (12:00), whereas species richness and diversity were higher in the nocturnal period, mainly at late night (2:00) and midnight (00:00). These assemblage attributes also changed in relation to tide, but they did not showed statistically significant differences. In order to investigate patterns in food habits of the studied fish fauna, the stomach content of 3,630 individuals belonging to 20 species were analyzed, which were selected based on their abundance and morphological diversity. The dominant pattern of feeding activity was diurnal and most species showed seasonal (wet/dry) and short (day/night) temporal variations in their diet, including ontogenetic diet changes. These variations were related to the feeding activity patterns (diurnal, nocturnal and/or crepuscular) of the fishes and to morphological changes acquired by the individuals during their increment in body size. A total of nine trophic guilds were observed, with Zooplancton Consumers (CZOO) showing the greatest number of fish species. The prevalence of CZOO occurred due to the high capture of juveniles, which could be explained by the fact that these habitats are considered important recruitment and as nursery areas since they provide essential resources in the early phase of their life cycle. Short scale variations in the structure and diet of the ichthyofauna observed in the current work were related to the feeding behavior and trophic ecology, whereas medium scale variations were attributed to variations in fish recruitment patterns.